THE GENE EXPRESSION OF ADAM17 AS A GENETIC MARKER OF ALZHEIMER DISEASES IN THE BRAIN OF LONG-TAILED MACAQUES (Macaca fascicularis) - Rosmanah, Lis; Hasya, Karin katina; Saepuloh, Uus; Manalu, Wasmen; Winarto, Adi; Sudarnika, Etih; Darusman, Huda Shalahudin (Jurnal Kedokteran Hewan, 2023)
This study aims to identify the expression of the a disintegrin and metalloproteinase 17 (ADAM17) gene as a marker of Alzheimer's disease in long-tailed macaques (Macaca fascicularis). This study used six brain samples (hippocampus and cortex regions) of long-tailed macaques which was divided into two groups consisting of aged long-tailed macaques and adult long-tailed macaques. The expression of ADAM17 gene was determined by comparing the relative quantification values between the two age groups, and brain regions consisting of the hippocampus and cortex regions. The results of data analysis showed no significant difference in the expression of ADAM17 gene between brain regions and between age groups of long-tailed macaques. However, numerically the results showed a lower expression of ADAM17 gene in the hippocampus region of aged macaques. Lower expression of ADAM17 gene could be a marker of old animals indicating the stages of Alzheimer's disease.